MENILAI KESESUAIAN QANUN KOMISI KEBENARAN DAN REKONSILIASI ACEH DENGAN ASAS-ASAS PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Pasha, Zahlul (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, Ekonomi Islam, 2019)
This research aim to analyze of parity between the Qanun of Aceh Truth and Reconcialiation Commission and the Law Number 12 Year 2011 on the Law-making Process.The conclusion of this research is establishment of the Qanun of Aceh Truth and Reconciliation Commission seems has trouble with the Law-making Process Principles, specifically on clarity of formulation, hierarchical types and material substances. Furthermore, this situation was leading motive prompting people who are harmed to initiate judicial review